Rancang Bangun Sistem Informasi Sewa Kios Pasar Tradisional Berbasis Web - Misda Sari; Ariansyah Ariansyah; Iwan Setiawan (STEKOM PRESS, 2024)
Along with the rapid development of technology and knowledge at this time makes information a very important role in order to achieve goals the development of computer technology today has grown rapidly, this encourages the creation of the need for the application of increasingly sophisticated computer technology. Design and build a kiosk rental information system at the web-based traditional market of Sumaja Makmur Village aims to facilitate the process of kiosk rental payment transactions. The situation faced by the traditional market of Sumaja Makmur Village is that the process of stall rental transactions is still carried out manually, so it takes time because traders have to come to the market chairman's office to make stall rental transactions. The research method used is a qualitative descriptive method, while the system development method uses the waterfall method.